Program evaluation of GLA:D® Australia: Physiotherapist training outcomes and effectiveness of implementation for people with knee osteoarthritis - Barton, Christian J.; Kemp, Joanne L.; Roos, Ewa M.; Skou, Soren T.; Dundules, Karen; Pazzinatto, Marcella F. [UNESP]; Francis, Matthew; Lannin, Natasha A.; Wallis, Jason A.; Crossley, Kay M. (Elsevier, 2021)
Objective: Evaluate the implementation of Good Life with osteoArthritis from Denmark (GLA:D®) for knee osteoarthritis in Australia using the RE-AIM QuEST (Reach, Effectiveness, Adoption, Implementation, Maintenance Qualitative Evaluation for Systematic Translation) framework. Design: Physiotherapists completed surveys before and after GLA:D® training (2017–2020) to assess practices, and barriers and enablers to implementation. Patients completed online baseline, 3-month (post-treatment) and 12-month patient reported outcomes. Effective implementation was defined as within-participant moderate effect size (ES, ≥0.50) for average pain (100 ​mm VAS) and Knee Injury and Osteoarthritis Outcome Score quality of life scores (KOOS-QoL), and small effect size (≥0.20) for health-related quality of life (EQ-5D-5L). Results: Reach: 1064 physiotherapists and 1945 patients from all states and territories participated. Key barriers included out-of-pocket cost to patients, and program suitability for culturally and linguistically diverse communities. Effectiveness: Following training, more physiotherapists reported discussing treatment goals and weight management, and prescribing supervised, neuromuscular exercise. Patient outcomes at 3- and 12-months (n ​= ​1044 [54%] and 927 [48%]) reflected effective implementation, including reduced pain (ES, 95%CI ​= ​0.72, 0.62–0.84; and 0.65, 0.54–0.77) and improved KOOS-QoL (0.79, 0.69–0.90; and 0.93, 0.81–1.04) and EQ-5D-5L (0.43, 0.31–0.54; and 0.46, 0.35–0.58) scores. Adoption: 297 sites (264 private, 33 public) implemented GLA:D®. Implementation: Most patients completed at least one education (90%), and 10 exercise-therapy (78%) sessions. Adequate staffing to support program delivery was a key enabler. Maintenance: 99% of sites (293/297) continued offering the program in July 2020. Conclusion: Training changed practice and was associated with effective widespread implementation of GLA:D® in Australia.
Keywords: Education; Exercise; Implementation; Osteoarthritis; Physiotherapy; Program evaluation